Banks Corporate Social Responsibility in the Awareness of Students of Lublin Universities - Kudlak, Izabela Joanna (Journal of Finance and Financial Law, 2018)
Today CSR – corporate social responsibility – is a key element of the strategic operations of meaningful companies. Banks which care about the improvement or keeping the good image are trying actively to promote their action using CSR tools. Examining the acquaintance of comprehending the corporate social responsibility at the bank amongst students which are studying at Lublin universites is a purpose of the article. The article contains the analysis of polls conducted amongst the examined group and the author conclusions with the subject matter brought up.